Determination of neuroprotective oxysterols in Calculus bovis, human gallstones, and traditional Chinese medicine preparations by liquid chromatography with mass spectrometry. Issue 5 (1st February 2015) - Wang, Yalong; Jiang, Han; Huang, Huizhi; Xie, Yanqi; Zhao, Yunshi; You, Xiuhua; Tang, Lipeng; Wang, Youqiong; Yin, Wei; Qiu, Pengxin; Yan, Guangmei; Hu, Haiyan
<x xml:space="preserve">Abstract</x> So far, the components responsible for the neuroprotective effects of Calculus bovis are unclear. Cholesterol, one of the major components in Calculus bovis, is easily oxidized into oxysterols, which possess direct or indirect neuroprotective effects proved by our and others' previous studies. Therefore, a liquid chromatography with mass spectrometry method coupled with ultrasonic extraction and solid‐phase extraction was developed for the determination of neuroprotective oxysterols in Calculus bovis, human gallstones, and traditional Chinese medicine preparations. Chromatographic separation was achieved on a C18 column with isocratic elution at a flow rate of 1 mL/min. The established method showed good linearity (R2 > 0.998), sensitivity with low limits of detection (0.06–0.39 μg/g), acceptable precisions (relative standard deviations ≤ 7.4%), stability (relative standard deviations ≤ 5.9%), and satisfactory accuracy (92.4–102.9%) for all analytes identified by different retention times, which could be applied for the determination of oxysterols. Five kinds of oxysterols proved to function as neuroprotectants were detected at different concentrations. Among them, 7β‐hydroxycholesterol and cholestane‐3β, 5α, 6β‐triol were rather abundant in the samples. It could be concluded that the potential neuroprotective components in Calculus bovis may be these oxysterols.